Perhitungan Kebutuhan Material Menggunakan Metode Material Requirement Planning - Fiqih Baktian Rahmansya; Aditya Maharani; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
There is a shortage of materials at PT. Ometraco Arya Samanta which caused the completion of project workthe gudang tembakau, the gudang penyetelan A & B project was delayed which affected project production. Running out of materials, messy production lines or man hours due to urgent projects and late material purchase schedules can be detrimental for PT. Ometraco Arya Samanta and the ordering party. This study aims to control material needs. The method used is the material requirement planning (MRP) method, namely by making a bill of materials to find out information about all the needs for components and the type of material used by making and completing a job to the end. And the MRP table for material requirements is obtained WF 300 35 spike, WF 500 19 spike, WF 250 29 spike, WF 600 22 spike, WF 250 21 spike, WF 200 10 spike, WF 150 24 spike, L 30 2 spike, L 40 345 spike, L 50 110 spike, L 60 478 spike. CT 200 148 spike, CNP 125 1.526 spike and CNP 100 98 spike. Meanwhile, the manhours requirement for the adjustment gudang penyetelan A & B is 2464,8 JO and gudang tembakau is 2004 JO. Then the number has a total of 4468,8 JO.